Association between metabolic syndrome, insulin resistance, and IGF-1 in breast cancer survivors of DIANA-5 study - De Santi, Mauro; Annibalini, Giosuè; Marano, Giuseppe; Biganzoli, Giacomo; Venturelli, Elisabetta; Pellegrini, Massimo; Lucertini, Francesco; Brandi, Giorgio; Biganzoli, Elia; Barbieri, Elena; Villarini, Anna (Journal of cancer research and clinical oncology, 2023)
Purpose Circulating insulin-like growth factor-1 (IGF-1) is positively associated with the risk of BC recurrence, and is more frequently dysregulated in older people, especially in those with metabolic syndrome (MetS) and obesity. This study aimed to analyze the association between IGF-1 levels and indices of MetS and insulin resistance in BC survivors. Methods Baseline data of 563 BC survivors enrolled in the DIet and ANdrogen-5 (DIANA-5; NCT05019989) study were analyzed. Results Lower circulating IGF-1 levels in subjects with MetS than in those without MetS were found. After stratification of the patients according to the diagnosis of MetS, we highlighted that the insulin was the main predictor of elevated IGF-1 levels only in subjects without MetS. Moreover, we found an interaction between high-density lipoprotein cholesterol (HDL-C), glycemia, and IGF-1 levels, showing a positive correlation between HDL-C and IGF-1, especially in subjects with higher values of glycemia and without a diagnosis of MetS. Conclusions While IGF-1 levels appear to be much more impaired in subjects diagnosed with MetS, in non-MetS subjects, IGF-1 levels may respond better to metabolic parameters and lifestyle changes. Further studies are needed to analyze the role of physical activity and/or dietary intervention in modulating IGF-1 concentrations in BC survivors. Implications for cancer survivors These results could have important clinical implications for planning customized strategies aimed at modulating IGF-1 levels in BC survivors. In fact, while the IGF-1 system seems to be much more compromised in subjects with a diagnosis of MetS, in noMetS subjects, IGF-1 levels could better respond to lifestyle changes.